2021
DOI: 10.1097/brs.0000000000004133
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Lower Extremity Motor Weakness Affects Deep Vein Thrombosis During the Perioperative Period of Lumbar Surgery

Abstract: Study Design. Prospective cohort study.Objective. The aim of this study was to assess preoperative factors in the development/exacerbation of deep vein thrombosis (DVT) in lumbar surgery and selectively perform lower-extremity venous ultrasonography (US) in patients at risk of perioperative deep vein thrombosis (DVT). Summary of Background Data. DVT is often present before lumbar surgery and also can develop or is exacerbated postoperatively. An elevated D-dimer level is predictive of DVT but not in all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Some scholars have studied the ossi cation of the posterior longitudinal ligament with acute spinal cord injury, showing that the impairment of lower limb motor function is a risk factor for DVT in the lower limbs. 26 Imyro et al 27 research 698 lumbar degenerative surgeries found that preoperativelower extremity < 3 was closely associated with the occurrence of DVT, which was consistent with our results. 27 Patients with spinal cord injury with dinnervation, complete loss of movement and sensation below the plane of injury, incomplete SCI patients with lower limb motor dysfunction.Our study patients with lower extremity < 3, the risk of postoperative DVT increased 10-fold.Therefore, patients admitted with lower extremity < 3 should take active measures to prevent DVT and reduce its incidence.…”
Section: Discussionsupporting
confidence: 91%
“…Some scholars have studied the ossi cation of the posterior longitudinal ligament with acute spinal cord injury, showing that the impairment of lower limb motor function is a risk factor for DVT in the lower limbs. 26 Imyro et al 27 research 698 lumbar degenerative surgeries found that preoperativelower extremity < 3 was closely associated with the occurrence of DVT, which was consistent with our results. 27 Patients with spinal cord injury with dinnervation, complete loss of movement and sensation below the plane of injury, incomplete SCI patients with lower limb motor dysfunction.Our study patients with lower extremity < 3, the risk of postoperative DVT increased 10-fold.Therefore, patients admitted with lower extremity < 3 should take active measures to prevent DVT and reduce its incidence.…”
Section: Discussionsupporting
confidence: 91%
“…Five investigations comprising 1671 patients found a link between preoperative walking dysfunction and the occurrence of VTE following spine surgery [ 30 33 , 36 ], with 82 patients having walking dysfunction, 1589 having no walking dysfunction, 168 having VTE (+), and 1503 having VTE (-). Since there was no statistical heterogeneity across the studies, the fixed effect model was used in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%